Reproductive biology of Oreocereus fossulatus (Cactaceae), a long‐lived columnar cactus endemic to the tropical Andes. Issue 3 (7th June 2018) - Larrea‐Alcázar, Daniel M.; López, Ramiro P.; Gutierrez, Josseth P.; García, Emilia
Abstract: The geographic dichotomy hypothesis suggests that columnar cacti inhabiting the tropics depend on flower visitors (birds and bats) for their pollination, showing highly specialized animal‐pollinated systems. This pattern has been demonstrated for the northern hemisphere; however, our knowledge of the species of columnar cacti growing in the southern tropics is still scarce. In this study, we studied the reproductive biology of Oreocereus fossulatus (Cactaceae, Tribe Trichocereae), an endemic, columnar cactus of the tropical Andes, to determine if its pollination system tends to be more generalized (mixed systems of autogamy and xenogamy) than specialized (xenogamy) as a consequence of the geographic position of where it lives. Observations of the frequency of visits showed that Patagona gigas (Trochillidae) is its main pollinator. It visits the flowers when they are open, coinciding with the periods of greater floral reward (dusk and dawn of the first day of anthesis). The treatments of autogamy, xenogamy and geitonogamy produced fruits, showing that O. fossulatus exhibits a generalized pollination system, in the same way as its congeneric species O. celsianus, which is distributed farther south in the Prepuna biogeographical region. Our results suggest that species partially specializing in pollination by hummingbirds and, besides, capable of autopollination, could be common in the tropical and subtropical Andes, probably as a response to the unpredictable environments present in their ecosystems. Abstract : Here, we studied the reproductive biology of Oreocereus fossulatus (Cactaceae), an endemic, columnar cactus of the tropical Andes. Our results suggest that this columnar cactus species partially specializes in pollination by hummingbirds and, besides, is capable of autopollination. This pollination strategy could be common in the tropical and subtropical Andes.